Analysis of the Leading Sectors of the Mandailing Natal Region in 2017-2021 Based on Potential Advantages - Ramadhan*, Aksel Rizky; Setyowati, Eni (Universitas Syiah Kuala, 2023)
The course of economic development has led to various changes, especially in the structure of the economy. Changes in the economic structure are one of the characteristics. This study wants to show the potential of several sectors in Mandailing Natal Regency with Location Quotion analysis, Klassen Typology analysis and Shift share analysis. The results of the study show that there are 2 economic sectors in Mandailing Natal Regency which are the base (leading) sectors. From the results of the LQ analysis, it was obtained that Government Administration, Defense and Compulsory Social Security with an LQ value of 2.05 while the base sector with the lowest LQ score (1.95) was Agriculture, Forestry and Fisheries. From the results of the Klassen Typology analysis it was identified that there were 2 sectors belonging to the advanced and fast-growing sectors (Quadrant I), six sectors included in the growing sector category (Quadrant II), four sectors included in the advanced but depressed sector category (Quadrant III), and 5 sectors fall into the category of relatively underdeveloped sectors (Quadrant IV). Meanwhile, from the calculation results of the Shift Share analysis, it is known that information and communication have the greatest competitiveness